Analisis Implementasi Pola Pengelolaan Keuangan Badan Layanan Umum Daerah (BLUD) Pada Rumah Sakit Umum Daerah (RSUD) Dr. RM. Djoelham Binjai - Silalahi, Bambang Azis; Sihombing, Marlon; Isnaini, Isnaini (Universitas Medan Area, 2021)
The purpose of this study was to determine and analyze how the implementation of PPK-BLUD policies in RSUD Dr. RM Djoelham Binjai in terms of improving the quality and quality of public services, especially health services to the people of Binjai City. The method used in this research is descriptive qualitative using the Merille S. Grindle theory where there are several variables that determine the effectiveness of policy implementation. From the research results it can be seen that after the implementation of PPK-BLUD in Dr. RM. Djoelham Binjai, there was a change where previously the budget management, finance and reporting processes, which had been purely based on financial regulations with the APBD mechanism. However, with the implementation of PPK-BLUD, all the income that the RSUD Dr. RM. Djoelham receives can be directly managed and used for the needs and needs of the RSUD. So it is hoped that it can simplify the bureaucracy, especially finance, so that in the end it can improve the quality of hospital services. In its implementation, there are several obstacles faced, especially the understanding of other sections and fields of PPK-BLUD in RSUD Dr. RM. Djoelham Binjai so that good coordination between divisions and fields is needed.